The impact of migration related to the conflict in Ukraine on the management of social policy in Poland - Zbigniew Ciekanowski; Sławomir Żurawski; Mariusz Czternastek (Journal of Modern Science)
Objectives The aim of the article is to analyze the impact of migration related to the conflict in Ukraine on the management of social policy in Poland and to assess to what extent the Polish social policy system has met the challenges resulting from mass migration.